Identifikasi Gastropoda pada Ekosistem Mangrove di Kampung Rawa Mekar Jaya Kecamatan Sungai Apit Kabupaten Siak Provinsi Riau - Lenny Marlyna; Eddiwan Eddiwan; Windarti Windarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abstract          In the Rawa Mekar Jaya Village, there is a mangrove conservation area. Anthropogenic activities conducted around that area, however, damage the mangrove in general and thus negatively affects gastropod living in that area. A research aims to identify gastropod species in that area was conducted in July 2019. A research was conducted with direct observation techiques at the study area. There were 3 stations and each station consists of 3 plots. In each plot there were 3 subplots (1x1 m). Gastropods were collected manually from each sub plot, everyday for a 2 weeks period. There were 5 gastropod species present, namely Cerithidea obtusa, Telescopium telescopium, Nerita violacea, Ellobium aurismidae, Chicoreus capucinus. The water quality were as follows: temperature (28-290C); pH 6; salinity (140/00); dissolved oxygen (4,1-5,0 mg/L), and sandy mud substrate.  Keywords :  Cerithidea sp, Rhizophora appiculata, mangrove forest